Melatonin ingestion after exhaustive late-evening exercise attenuate muscle damage, oxidative stress, and inflammation during intense short term effort in the following day in teenage athletes. (1st February 2020) - Cheikh, Mohamed; Makhlouf, Khouloud; Ghattassi, Kais; Graja, Ahmed; Ferchichi, Salyma; Kallel, Choumous; Houda, Mallek; Souissi, Nizar; Hammouda, Omar
ABSTRACT: The present study aimed to investigate whether nocturnal melatonin (MEL) ingestion has beneficial effects against exercise-induced oxidative stress and muscle damage in young athletes. Fourteen healthy-trained teenagers performed two-test sessions separated by at least, 1 week. During each session, participants completed the Running-Based Anaerobic Sprint Test (RAST) at 20:00 h. Then, they ingested a single 10-mg tablet of MEL or Placebo (PLA) in a double-blind randomized order at 22:00 h. The following morning (i.e., 07:30 h), participants performed the same test as the previous night. Blood samples were taken before and after exercise. MEL intake increased the peak power (Ppeak ) ( p < .01), mean power (Pmean ) ( p < .001) and decreased the total time (TT) ( p < .001) and the fatigue index (FI) ( p < .05). Furthermore, MEL ingestion attenuated the hematologic parameters before and after exercise (White Blood Cells (WBC: p < .001 and p < .001, respectively); Neutrophiles (NE: p < .001 and p < .001, respectively); Lymphocytes (LY: p < .001 and p < .001, respectively)) and the ultra-sensitive C-reactive protein (us-CRP: p < .001 and p < .001; respectively) compared to PLA. Also, MEL reduced muscle and hepatic damage enzymes before and after exercise (creatine kinase (CK: p < .001 and p < .001; respectively), lactate dehydrogenase (LDH: p < .05 and p < .01; respectively), aspartate aminotransferase (ASAT: p < .01 and p < .001; respectively)), Malondialdehyde (MDA: p < .001 and p < .001; respectively) and Homocysteine (Hcy: p < .001 and p < .001; respectively)) from placebo. Plasma lactate [La] and glucose (GL) remained unchangeable during the two conditions. In summary, acute MEL ingestion after strenuous late-evening exercise attenuated transient leucocytosis and protected against lipid peroxidation and muscle damage induced by strenuous exercise the following morning in healthy male teenage athletes.